Chronic Jet Lag Exacerbates Jejunal and Colonic Microenvironment in Mice - Li, Qing; Wang, Bo; Qiu, Hong-Yi; Yan, Xiu-Juan; Cheng, Li; Wang, Qian-Qian; Chen, Sheng-Liang (Frontiers in Cellular and Infection Microbiology, 2021)
Background Evidence suggests that circadian rhythm disorder is associated with a variety of gastrointestinal diseases, and the circadian rhythm plays a key role in maintaining the homeostasis of intestinal flora. The underlying mechanisms are still not completely identified. This study was aimed to explore whether jet lag-caused circadian disruption influences gut microbiome and its metabolites. Methods Mice were synchronized with 12-h light/dark cycles (control group) or subjected to daily 8-h advance of the light/dark cycle for every 3 days (jet-lagged group). Four months later, fecal samples and jejunal contents were collected and analyzed by 16S rRNA gene sequencing. In addition, fecal samples were subjected to metabolome analysis with ultra-performance liquid chromatography coupled to tandem mass spectrometry (UPLC-MS/MS). Results The results of 16s rRNA sequencing showed that chronic jet lag led to decreased microbial abundance, richness, and diversity in both feces and jejunal contents. ANOSIM analysis revealed significant difference between control and jet-lagged groups. As the colonic microbiome, the abundance of Bacteroidetes phylum was significantly decreased and that of Actinobacteria phylum was increased in jet-lagged mice. Jet lag increased the ratio of Firmicutes to Bacteroidetes, an indicator for the imbalance of gut microbiota. Metabolome analysis of fecal samples showed that the levels of tryptophan and its derivatives were decreased in jet-lagged mice. In addition, fecal levels of secondary bile acids changed under jet lag conditions. Correlation analysis identified associations between tryptophan (and its derivatives) levels and colonic microbiota. Conclusions This study presents a comprehensive landscape of gut microbiota and its metabolites in mice subjected to chronic jet lag. The results suggest that circadian disruption may lead to changes in fecal and jejunal microbiota and fecal metabolites. Moreover, our results demonstrate a novel interplay between the gut microbiome and metabolome.